Paralympic sport: an emerging area for research and consultancy in sports biomechanics - Keogh, J. W. L. (Sports Biomechanics, 2011)
The Paralympic Games are the pinnacle of sport for many athletes with a disability. The overall purpose of this paper is to highlight the role that the field of sports biomechanics specifically (and sports science in general) may play in improving performance in various summer Paralympic sports through research and consultancy. To achieve this broad aim, this review provides some history and background on the Summer Paralympic Games, discusses the eligibility and classification rules, describes the potential for the constraints-led approach of dynamical systems theory to inform practice and research in this area, and reviews selected studies examining the biomechanics of the primary forms of Paralympic locomotion. Some recommendations on how sports biomechanics can help facilitate improvements in Paralympic athletic performance through applied research and consultancy are provided, along with commentary on what may be some of the most important issues addressing Paralympic sport.